PERHITUNGAN, PENYETORAN, DAN PELAPORAN SPT MASA PPH PASAL 21 - HARYO SUPARMUN (Media Bisnis, 2014)
As the source of government’s income, Taxes play important roles and it has become the central issue of the nation. The purpose of the study is to describe the calculate, deposit and reporting of income tax return article 21. X using income tax law no 36 year 2008 and regulation director at general of taxation PER-31/PJ/2009 and PER-57/PJ/2009. This study uses qualitative research method on the data of income tax return. This result discovers that firm has not properly applied the obligation in calculating, depositing and reporting income tax return article 21.